Learning from health care in other countries: the prospect of comparative research - van Teijlingen, Edwin; Benoit, Cecilia; Bourgeault, Ivy; DeVries, Raymond; Sandall, Jane; Wrede, Sirpa (Health Prospect, 2015)
It is widely accepted that policy-makers (in Nepal and elsewhere) can learn valuable lessons from the way other countries run their health and social services. We highlight some of the specific contributions the discipline of sociology can make to cross-national comparative research in the public health field. Sociologists call attention to often unnoticed social and cultural factors that influence the way national reproductive health care systems are created and operated. In this paper we address questions such as: ‘Why do these health services appear to be operating successfully in one country, but not another?’; ‘What is it in one country that makes a particular public health intervention successful and how is the cultural context different in a neighbouring country?’ The key examples in this paper focus on maternity care and sex education in the Netherlands and the UK, as examples to highlight the power of cross-national research. Our key messages are: a) Cross-national comparative research can help us to understand the design and running of health services in one country, say Nepal, by learning from a comparison with other countries, for example Sri Lanka or India. b) Cultural factors unique to a country affect the way that reproductive health care systems operate. c) Therefore,we need to understand why and how services work in a certain cultural context before we start trying to implement them in another cultural context.